SISTEMA LACUSTRE VIANENSE: ENSAIOS DE MODELOS CONCEITUAIS PARA OS LAGOS DO MUNICÍPIO DE VIANA-MA - Franco, José Raimundo Campelo (2008)
VIANENSE LACUSTRINE SYSTEM: ESSAY OF CONCEPTUAL MODELS FOR THE LAKES IN VIANA IN MARANHÃO. We consider a study about the functional aspects of the lacustrine set of Viana in Maranhão in which it is focused the dynamic and structural work and also the dynamical and structural elements of the enviroment. Highlighting the hydroclimatic factors which are responsible for the flooding movements and the human being in the search for his needs. The importance of this investigation is on the development of new data and the knowed be which can subsidize the environmental and urban planning , reinforce the didactical hase of contente on Maranhão and also vianense geography and guiding new researches on Baixada Maranhense focus. The methodological processes were made though interpretation and processing of satellites images in SIG, analyses techinics for ecological traditional knowledge and theories. In geography which regulate the relation between the society and nature. From the theoretical set were established two main conceptual models which prove the comprehension of the lacustrine places in Viana: The Pindaré- Mearim lacustrine system-SLPM and the vianense lacustrine system- SLV, both models are explained in their systemic functional bases of local and interactive manifestations with previous and subsequent systems. Other conceptual bases were made, adapted or redimensioned through classical considerations or from new concepts from conteporaneam geography on a unique viens which analyse the physical phenomenon linked to human societies. Thus the traditional knowede in geography and the technical job of processing and interpretation of sattelite image were definite tools on the systematization of conceptual models and on the systemical dynamics translation. The study field showed rich itself in biodiversity variable in their landscapes and widespread on their natural resources mainly in hydro ones - however, it showed itself poor in politics initiative which reconsider the effect of deleterious environmental interferences to the lacustrine systems and the social conflicts because of them.